Transforming Character Education through the Implementation of the Independent Curriculum in Indonesia - Zainuddin, Zainuddin; Nafisah, Ani; Muttaqin, Muhammad (Ilmu Inovasi Nusantara, 2025)
The transformation of character education has become a crucial agenda in the development of Indonesia’s human resources, especially in responding to global challenges and the post-pandemic learning crisis. The Independent Curriculum has emerged as an innovative educational policy that emphasizes flexibility, differentiated learning, and character strengthening through the integration of Pancasila Student Profile values. However, there remains a research gap concerning the extent to which this curriculum effectively fosters students’ character holistically and how its implementation faces real challenges in the field. This study aims to analyze the implementation of the Independent Curriculum in the transformation of character education in Indonesia by highlighting the strategies, challenges, and its impact on students’ motivation and learning quality. The method employed is a qualitative descriptive literature review by analyzing various recent research findings and empirical data. The results show that the Independent Curriculum enhances learning motivation, active student engagement, and the quality of the learning process through a more interactive and student-centered approach. Teachers play a strategic role as facilitators and agents of change, although they still require training and systemic support. The findings underscore the importance of synergy among stakeholders in strengthening the capacity of curriculum implementers, developing comprehensive character evaluation systems, and creating an inclusive and adaptive learning ecosystem. The Independent Curriculum has the potential to become a strong foundation in shaping an Indonesian generation that excels not only academically but also possesses moral integrity, social sensitivity, and adaptability in the global era